2015
DOI: 10.1016/j.ygyno.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer in the United States: Contemporary patterns of care associated with improved survival

Abstract: Background Ovarian cancer (OC) requires complex multidisciplinary care with wide variations in outcome. We sought to determine the impact of institutional and process of care factors on overall survival (OS) and delivery of guideline care nationally. Methods This was a retrospective cohort study of primary OC diagnosed from 1998 to 2007 using the National Cancer Data Base (NCDB) capturing 80% of all U.S. cases. Patient- (demographics, comorbidities, stage/grade), process of care (adherence to guidelines) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 26 publications
6
116
1
Order By: Relevance
“…Indeed, we found that higher volume hospitals treated the more 27 severely ill patients. This result is consistent with the existing literature on the VOR for EOC patients in the USA (Bristow, Chang, Ziogas, Randall, & Anton-Culver, 2014;Cliby et al, 2015). We also found that the more severely ill patients and the patients treated in higher volume hospitals were more likely to be treated with neoadjuvant chemotherapy rather than primary surgery as first-line treatment.…”
Section: External Validitysupporting
confidence: 91%
“…Indeed, we found that higher volume hospitals treated the more 27 severely ill patients. This result is consistent with the existing literature on the VOR for EOC patients in the USA (Bristow, Chang, Ziogas, Randall, & Anton-Culver, 2014;Cliby et al, 2015). We also found that the more severely ill patients and the patients treated in higher volume hospitals were more likely to be treated with neoadjuvant chemotherapy rather than primary surgery as first-line treatment.…”
Section: External Validitysupporting
confidence: 91%
“…The care of prostate cancer patients necessitates multidisciplinary collaboration (21-24) among urologists, radiation oncologists, medical oncologists, radiologists, and pathologists, and a high case volume facility has higher likelihood of having experts in all the related specialties onsite. In such high-volume centers, care is likely to be well coordinated between specialists and patients are likely to be treated in a consistent fashion (11,(25)(26)(27)(28)(29), including optimal staging and selection of duration of androgen deprivation therapy, leading to better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of physician can impact outcomes (130,131) as can adherence to the guidelines for the standard of care (132,133); surgery performed by a gynecologic oncologist results in superior outcomes and survival, compared with surgery performed by a non-gynecologic oncologist, such as a general surgeon. (Figure 4).…”
Section: [H1]managementmentioning
confidence: 99%